Arctic Ocean, Amundson's flying boat, N25 - Ellsworth, Lincoln, 1880-1951 (1925)
"No. 12 Amundsen-Ellsworth 1925 Exped. "Like a gnat in an ocean of space" − N 25 just before landing − 600 miles into the "unknown." Caption taken from Ellsworth, L., & National Americana Society. (1929). Air Pioneering in the Arctic: the Two Polar Flights of Roald Amundsen and Lincoln Ellsworth (pp. 57, No.12). New York: National Americana Society. Amundsen-Ellsworth 1925 Expedition